2019
DOI: 10.1186/s12935-019-0791-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: TMED3 promotes cell proliferation and motility in breast cancer and is negatively modulated by miR-188-3p

Abstract: Background The role of TMED3 involved in cancers has been seldom described, let alone in breast cancer. To explore the clinicopathological significance of TMED3 expression and the biological roles involved in breast cancer cells, we undertook the study. Methods Immunohistochemistry was performed to observe the pattern of TMED3 expression in breast cancer tissues, totaling 224 cases; followed by detailed statistical analysis between TMED3 expression versus clinicopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
3
36
0
1
Order By: Relevance
“…BMSC-specific miR-188 inhibition by intra-bone marrow aptamer-antagomiR-188 injection increased bone formation ( Li et al, 2015 ). This study also verified that evoked miR-188-3p expression impaired cell proliferation, especially tumor cells ( Pei et al, 2019 ; Shi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 78%
“…BMSC-specific miR-188 inhibition by intra-bone marrow aptamer-antagomiR-188 injection increased bone formation ( Li et al, 2015 ). This study also verified that evoked miR-188-3p expression impaired cell proliferation, especially tumor cells ( Pei et al, 2019 ; Shi et al, 2019 ).…”
Section: Discussionsupporting
confidence: 78%
“…As a miRNA, miR-188 was reported to exert function in many types of cancer, such as colorectal cancer, 43 oral squamous cell carcinoma, 44 gastric cancer, 45 and breast cancer. 46 Besides, miR-188 acted as a regulator to repress proliferation, cycle transition, and colony formation of NPC cells. 25 Agreement with this result, our data revealed that miR-188 repressed cell growth in NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [50] found that miR-188-3p might be a new potential therapy for atherosclerosis by inhibiting macrophage proinflammatory response and oxidation. Pei et al [51] found that miR-188-3p inhibited the cell proliferation and motility in breast cancer The seed region of miRNAs is underlined by targeting Transmembrane emp24 domain-containing protein 3 (TMED3). Pichler et al [52] identified miR-188-3p as a novel prognostic marker and molecular factor involved in colorectal carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%